(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the interrelationship between social, cultural, and economic factors that influence the formation of aesthetic taste among youth. It examines how various elements—such as the social environment, family upbringing, mass media, cultural heritage, art, fashion, and market economy—shape young people’s worldview and their perception of beauty. The paper also addresses the challenges posed by globalization to national aesthetic values and emphasizes the importance of fostering an appreciation for traditional culture in younger generations. The study provides pedagogical and cultural recommendations aimed at enhancing aesthetic education. This research is of practical value to professionals in aesthetics, cultural studies, sociology, and pedagogy.